REPRODUCTIVE OUTCOMES FOLLOWING CHILDHOOD HEMATOPOIETIC STEM CELL TRANSPLANTATION: SUCCESSFUL PREGNANCIES AND 40 CHILDREN BORN TO 25 OF 180 ADULT LONG-TERM SURVIVORS - šnajderová, Marta; Keslova, Petra; Formankova, Renata; Riha, Petr; Sedlacek, Petr; Stary, Jan (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Gonadal insufficiency and infertility are amongst the most frequent and emotionally sensitive late complications following hematopoietic stem cell transplantation (HSCT). So far little is known about reproductive outcomes following childhood HSCT. METHODOLOGY Successful pregnancies/births were evaluated amongst 180 adult long-term survivors following HSCT, transplanted at median age 15.5 (range 8.0–19.9) years. RESULTS So far 25/180 (14%) subjects (males=14; females=11) 10.4 (2.5- 24.0) years after HSCT became parents (n=20 biological) of 40 children (n=34 in term). Primary diagnosis at HSCT was: Severe aplastic anemia (SAA; n=12), acute lymphoblastic (ALL; n=6), acute myeloid (AML; n=1) and chronic myeloid (CML; n=3) leukemia, myelodysplastic syndrome (MDS; n=3). Spontaneous conception with 28 children reached 16 subjects (males=9), 5/7 females still spontaneously menstruating. SAA received cyclophosphamide only (males=7; females=5). Two males (MDS and ALL) had full myeloablative dose of busulphan during conditioning, 2 females (MDS and CML with hormonal replacement) spontaneously conceived following previously unsuccessful assisted reproduction (ART), one after total body irradiation 14.4 Gy (probably residual oocyte reserve and ovarian hyperstimulation). After ART, remaining 9/25 subjects became parents (n=4 biological) of 12 children (n=2 males cryopreserved sperm; n=2 males TESE; n=1 male donor sperm; n=4 females donor oocytes). CONCLUSION The ability to have offspring significantly affects the quality of life after HSCT. At the peritransplant care, fertility issues, pregnancy outcome and the possibility of fertility preservation must be routinely discussed. Better knowledge of pregnancy rate in pediatric population following HSCT will require more data. Very limited data is available on frequency of abortions.